(untitled) (Experimental biology, 2018)
The history of three Kazakh zhuzes formation is not fixed in written documents, what causes historians to create various versions about the reasons and date of this historic event. To investigate zhuzes structure we conducted comparative analysis of genetic diversity and analysis of molecular variation based on the distribution of Y-chromosome haplogroups among Kazakh tribes. Using two methods we have shown that zhuzes structure is only partially based on the kinship between the tribes within zhuzes. Great and Junior zhuzes comprises groups of related tribes. The Kanly, Srgeli and Ysty tribes stand apart from other tribes of the Great zhuz. In the Junior zhuz the Zhetyru tribe can be distinguished. The Middle zhuz was the most heterogeneous of three zhuzes, where each studied tribe can be regarded as the separate group, with the exception of the Kerei tribe, which has kinship with the group of tribes of the Great zhuz. According to AMOVA the division of the tribes into 9 or 10 groups is the most preferable for describing genetic relations of Kazakh tribes. The obtained data will be useful for historians, ethnographers, population geneticists and other specialists dealing with the issue of Kazakhs ethnogenesis.